MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL MODEL PEMBELAJARAN SELAMA KEGIATAN ASISTENSI MENGAJAR DI UPT SDN 066656 MEDAN SELAYANG - Albert Kristopel Hasibuan; Solafide M. Lumbantoruan; Sintya Engelina Br. Ginting; Asri Anjani Lamria Siahaan; Rizki Bastanta B. Manalu; Frikson Jony Purba (Journal of Golden Generation Education, 2025)
Teaching assistance is part of a field experience program aimed at integrating theory learned in lectures with hands-on practice in the classroom. Through this activity, students are expected to develop pedagogical, professional, social, and personal competencies in line with the demands of the teaching profession. This teaching assistance activity is conducted at UPT SD Negeri 066656, one of the elementary schools in Medan, specifically located at Jl. Karya Sembada No. 182 A PB. Selayang II. The objective is to provide direct teaching experience, understand student characteristics, and develop skills in designing, implementing, and evaluating the learning process. Through this teaching assistance program, students not only observe the learning process but also actively participate in teaching activities and assist teachers in the learning process. This report is compiled as a form of accountability for the implementation of the teaching assistance activities and as a reflection on the experiences gained during the program. Additionally, students have carried out a series of activities focused on improving the quality of learning and applying 21st-century learning approaches. The activities conducted include: Students observing the learning process in the classroom, including analyzing the curriculum and students' learning needs. Students developing learning materials such as lesson plans/teaching modules and designing learning media. Students also actively participating in the adaptation of technology in learning.